TINJAUAN HUKUM TERHADAP PENERAPAN SANKSI ADMINISTRATIF LINGKUNGAN HIDUP PADA KEGIATAN USAHA YANG MELAKUKAN PENCEMARAN LINGKUNGAN (DI KFC DINE & RILEX KOTA SAMARINDA) - ANDRI SUHENDRA (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT Andri Suhendra, NPM: 13.11.1001.1011.086, "Legal Review of Implementation of Environmental Administrative Sanctions on Business Conduct Conducting Environmental Pollution (In Kfc Dine & Rilex of Samarinda City)". Guided by Dr. H. Abdul Rokhim, SH., M. Hum as the supervisor of I and Syamsul Bahri, SH., MH.This study aims to determine the extent to which the role of Environmental Office of Samarinda City in maximizing the implementation of environmental administrative sanctions on KFC & Rilex business activities in Samarinda City. This study also aims to find out what obstacles faced by the Environment Department of Samarinda City in administering administrative sanctions to KFC & Rilex business owners.This research was conducted in Samarinda City. The object of the research is the Environment Department of Samarinda City. This research is conducted by conducting interviews with the speakers of the Regional Environmental Supervisory Official (PPLHD) who are competent and relevant to the proposed topic. The second approach is to describe descriptively the results of interviews and then analyze the data.The results of the study indicate that the enforcement of administrative sanctions by the government consistently in accordance with existing authorities will have an impact on law enforcement, in order to preserve the function of the environment. In connection with this, enforcement of administrative sanctions is at the forefront of enforcing environmental law (primium remedium). The obstacles faced are, the Environmental Supervisory Officer in exercising his authority to supervise the enforcement of environmental law is hampered by the administrative bureaucracy problem, as in Article 71 of UUPPLH Number 32 Year 2009, In the event that the environmental supervisor has done his duty and authority in doing supervision or examination on the indication of the occurrence of pollution or destruction of the environment, then when the report of the supervisory work of the environmental supervisory official is submitted to the top officials structurally such as the Head of Technical Division, Regent / Mayor, Governor, there is an indication of business activities checked and supervised by PPLHD the head of the agency The technical officer and the authority having authority over it, which is given the environmental monitoring report, is not followed up by the Head of Institution of Technical Affairs, Regent / Mayor, Governor, is very big and may happen. Too great the potential for disruption of decision-making on the result of environmental monitoring report to be submitted to the Head of DLH of Samarinda City, PPLHD must observe the hierarchical system of organizational structure which could happen the intervention from the structural position above it to the content result and the suggestion of the action contained in the result of supervision, can the imprecise of imposition of environmental sanctions such as the example of government sanction imposition of freezing permit to sanction reprimand I, the omission in the control system of the implementation of government coercion, and others. The real obstacle faced by PPLHD in the implementation of its duties and functions concerning UUPPLH 32 year 2009 in Article 71.